Έμφυλη κατηγοριοποίηση, δικαστική ερμηνεία και επαναπροσδιορισμός φύλου στο ελληνικό νομικό πλαίσιο - Κασαπίδου Ρούσσα (Aegean Working Papers in Ethnographic Linguistics, 2017)
This article examines the premises of gendered categorization and gender reassignment within the Greek legal context as they have evolved throughout the 20th century reaching to the current day. An attempt is made to understand “category” as a notion of historical as well as political content as opposed to its earlier uniform pseudoobjective view. Gendered categorization within the law is then connected with the power invested in the judicial interpretations of legal texts (and legal silences) in cases of contested gender legal recognition. Interpretation is analyzed as an instance of power, a mode of safeguarding (through naturalizing) the status quo of gender categories in the law. Finally, the last part of the article catches up with the latest legal developments on the issue of gender legal recognition in Greece up to late 2016.